2022
DOI: 10.1111/tpj.15662
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomic analyses reveal the diversity and plasticity of the specialized metabolome in seeds of different Camelina sativa genotypes

Abstract: Despite the essential role of specialized metabolites (SMs) in the interaction of plants with the environment, studying the ability of crop seeds to produce these protective compounds has been neglected. Furthermore, seeds produce a myriad of SMs, providing an interesting model to investigate their diversity and plasticity. Camelina sativa gained a lot of interest in the past few years as a rustic oilseed crop. A characterization of seed SM landscapes in six camelina genotypes grown in the field and harvested … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 100 publications
1
23
0
1
Order By: Relevance
“…Besides, impaired growth was observed for broiler chickens when fed with 5% of camelina seed cake (Ryhänen et al ., 2007 ). Camelina seeds exhibit a higher glucosinolate content (13.2–36.2 mmol/kg seed meal, depending on the variety) than canola (7.2 mmol/kg; Boutet et al ., 2022 ; Colombini et al ., 2014 ; Schuster and Friedt, 1998 ). We obtained comparable values for seeds of camelina WT139 (22.4 nmol/mg).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, impaired growth was observed for broiler chickens when fed with 5% of camelina seed cake (Ryhänen et al ., 2007 ). Camelina seeds exhibit a higher glucosinolate content (13.2–36.2 mmol/kg seed meal, depending on the variety) than canola (7.2 mmol/kg; Boutet et al ., 2022 ; Colombini et al ., 2014 ; Schuster and Friedt, 1998 ). We obtained comparable values for seeds of camelina WT139 (22.4 nmol/mg).…”
Section: Discussionmentioning
confidence: 99%
“…The glucosinolate content in camelina meal after solvent extraction can be further decreased during post‐processing and can thus meet the regulatory limits (European Food Safety Authority (EFSA), 2008 ; Matthäus and Angelini, 2005 ). On the other hand, the glucosinolate content of the seeds, similar to other specialized metabolites of camelina, show a very high plasticity due to environmental conditions and in different genotypes (Boutet et al ., 2022 ). Therefore, it is desirable to generate new camelina lines showing a stable and reduced glucosinolate content.…”
Section: Introductionmentioning
confidence: 99%
“…Despite little information is available, it has been also reported that glucosinolate content decreased in seeds of B. rapa plants subjected to potassium deficiency [169]. More recently, a large environmental induction and plasticity of SMs has been observed in seeds of Camelina sativa cultivated during five consecutive growing seasons [152,153]. This work highlighted major effects of the environment on the stimulation of the seed specialized metabolome.…”
Section: Specialized Metabolitesmentioning
confidence: 76%
“…In addition to genetic determinism and tissue distribution, the content and nature of storage compounds (including oil and proteins) and SMs are also shaped by the environment, and strongly impact the nutritional, agronomic or industrial quality of seeds (Figure 4). Many biotic and abiotic factors, such as drought or elevated temperatures can affect seed oil and protein composition [152][153][154][155][156], seed germination, and impact seedling vigour [157,158].…”
Section: Plasticity and Environmental Regulation Of Seed Compositionmentioning
confidence: 99%
See 1 more Smart Citation